Tachyarrhythmia in neonates. Clinical case of atrial flutter in a newborn - O.B. Kuryliak; T.V. Burak; A.A. Malska (Zaslavsky O.Yu., 2019)
Background. Tachyarrhythmia is the most severe rhythm disturbance in pediatric population. Atrial flutter is an extremely rare form of tachyarrhythmia and is not typical for newborns. Incidence of atrial flutter in neonates is 1 : 50,000 and amounts 3 % out of all rhythm disturbances in neonates. The purpose was to present a clinical case of atrial fibrillation in a newborn and literature overview of the treatment of tachyarrhythmia in children of different age. Materials and methods. This article presents a clinical case of severe rhythm disturbance - atrial fibrillation 2 : 1, 3 : 1 with the recurrent episodes of supraventricular tachycardia, frequent ventricular ectopic beats and diminished ejection fraction in a newborn. The following diagnostic methods were used in the research: ECG and 2D Doppler echocardiography. Results. The following treatment was applied in this particular case: adenosine bolus i/v, second infusion - without effect, cordarone infusion 15 mg/kg/d, sedation. Due to the progression of heart failure and decrease of ejection fraction, inotropic therapy was started (digoxin 20 μg/kg). As a result, the sinus rhythm was restored within 24 hours. Infusion of cordarone 10 mg/kg was continued for the following 5 days with transition to 5 mg/kg dosage. Thereby, repeat echo-examination results showed heart chambers decreased in size, no intracardiac anomalies, pulsatile blood flow in the descending aorta and the ejection fraction improved to 45-50-62-66 %. As follows, sinus rhythm with the heart rate of 130 beats per minute was monitored without the signs of chambers hypertrophy and conduction disturbances. Conclusions. In this particular case, the treatment of atrial flutter episode - gaining the sinus rhythm was achieved by drug therapy. Alternative method of treatment is cardioversion 0.5-1.0 J/kg [5, 6].